Investigation of the causes of the longitudinal variation of the electron density in the Weddell Sea Anomaly. Issue 6 (5th June 2017) - Richards, P. G.; Meier, R. R.; Chen, Shih‐Ping; Drob, D. P.; Dandenault, P.
Abstract: This paper investigates and quantifies the causes of the Weddell Sea Anomaly (WSA), a region near the tip of South America extending from approximately 30° to 120°W geographic longitude and 50° to 75°S geographic latitude at solar minimum between 2007 and 2010. This region is unusual because the midnight peak electron density exceeds the midday peak electron density in summer. This study is far more quantitative than previous studies because, unlike other models, it assimilates selected data parameters to constrain a physical model in order to investigate other aspects of the data. It is shown that the commonly accepted explanation that the WSA is related to the magnetic field declination and inclination effects on the neutral wind does not explain the longitudinal variation of the electron density. Rather, longitudinal changes in the neutral winds and neutral densities are the most likely explanation for the WSA. These longitudinal wind and density changes are attributed to the varying latitudinal distance from the auroral zone energy input. No contributions from the plasmasphere or other sources are required. Furthermore, it is shown that a widely used empirical thermosphere density model overestimates the longitudinal changes in the WSA region. Plain Language Summary: This paper investigates and quantifies the causes of the Weddell Sea Anomaly (WSA), a region near the tip of South America extending from approximately 30° to 120°W geographic longitude and 50° to 75°S geographic latitude at solar minimum between 2007 and 2010. This region is unusual because the midnight peak electron density exceeds the midday peak electron density in summer. This study is far more quantitative than previous studies because, unlike other models, it assimilates selected data parameters to constrain a physical model in order to investigate other aspects of the data. It is shown that the commonly accepted explanation that the WSA is related to the magnetic field declination and inclination effects on the neutral wind does not explain the longitudinal variation of the electron density. Rather, longitudinal changes in the neutral winds and neutral densities are the most likely explanation for the WSA. These longitudinal wind and density changes are attributed to the varying latitudinal distance from the auroral zone energy input. No contributions from the plasmasphere or other sources are required. Furthermore, it is shown that a widely used empirical thermosphere density model overestimates the longitudinal changes in the WSA region. Key Points: Ionosonde and satellite measurements of the Weddell Sea Anomaly (WSA) can be reproduced with the FLIP model The longitudinal variation of the WSA electron density is caused by variations in both the neutral densities and the neutral winds The magnetic field configuration is only a minor factor in the longitudinal variation of the electron density in the WSA